Non-Newtonian thermal elastohydrodynamic simulation of helical gears considering modification and misalignment. (August 2018) - Peng, Yanjun; Zhao, Ning; Zhang, Mengqi; Li, Wang; Zhou, Ruchuan
Abstract: Elastohydrodynamic lubrication (EHL) is significant for gear tribology design. This paper introduces a novel non-Newtonian thermal EHL model for helical gears with modifications and misalignments. An asymmetric spherical roller contact model is proposed for the contact between the modified tooth surfaces incorporating misalignments. In conjunction with a load distribution model, the geometric parameters of EHL model are derived from unloaded meshing simulation and kinematic analysis. In addition to a pressure-temperature iteration method, several specific numerical techniques are applied for the severe convergence due to edge contact. The effects of modifications and misalignments on tribological behavior are investigated. Results indicate that the edge contact at both ends of mesh leads to high pressure and temperature, as well as thin film thickness. The double-crowning improves lubrication performance and provides a superior tolerance for misalignments. Highlights: A novel EHL model is proposed considering modification and misalignment. An asymmetric spherical roller contact model is proposed for tooth surface contact. Modification and misalignment significantly affect tribological behavior. The double-crowning can improve lubrication performance.